(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Damanik R, Pasaribu N, Siregar ES, Syamsuardi. 2022. The family Plagiochilaceae (Marchantiophyta) in Batang Toru Forest, North Sumatra, Indonesia. Biodiversitas 23: 3127-3134. Investigation on the liverwort family Plagiochilaceae in Batang Toru Forest, North Sumatra, Indonesia resulted in ten taxon of Plagiochilaceae namely Plagiochilion oppositum, Plagiochila bantamensis, Plagiochila dendroides, Plagiochila denticulate, Plagiochila frondescens, Plagiochila junghuhniana, Plagiochila propinqua, Plagiochila sciophila, Dinckleria singularis, Plagiochila sumatrana, distributed under three genera Dinckleria (1 species), Plagiochila (8 species) and Plagiochilion (1 species). Plagiochila junghuhniana was the most observed species, while Plagiochila sciophilia was the least frequently encountered species in the forest.